The Effect of Mindfulness-Based Therapy on Anxiety Levels in Patients with Anxiety Disorders - Andi Pratama; Sopheak Chann (Lembaga Publikasi Ilmiah Nusantara, 2025)
Anxiety disorders are among the most common mental health problems worldwide, often leading to impaired quality of life and decreased functioning. Conventional pharmacological treatments are effective but may present side effects and limited long-term adherence. Mindfulness-Based Therapy (MBT) has emerged as a promising non-pharmacological intervention, focusing on awareness and acceptance of thoughts and emotions to reduce anxiety symptoms. This study aimed to evaluate the effectiveness of MBT in reducing anxiety levels among patients with clinically diagnosed anxiety disorders. A quasi-experimental design with pre-test and post-test control groups was conducted at a psychiatric outpatient clinic in Yogyakarta, Indonesia, from January to June 2024. A total of 80 patients were recruited and randomly assigned to either the intervention group (MBT, n=40) or the control group (standard care, n=40). The Beck Anxiety Inventory (BAI) was used to measure anxiety levels before and after the intervention. Results showed a significant reduction in anxiety scores in the MBT group compared to the control group (p < 0.01). These findings indicate that MBT is an effective complementary intervention for reducing anxiety symptoms and can be integrated into routine clinical practice. Future studies should explore long-term outcomes and its applicability across diverse populations.